Les représentations de l’eau - Bernadette De Vanssay (VertigO)
Theory of collective representations  were developped by Moscovici, in France, in the nineteen seventy years. It suggests that mental representations are more often inducing behaviours than the facts in temselves. On another hand, issues related to water resources and its deterioration are becoming a concern more and more urgent to address for people in charge of water management. It is why, the author with the participation of Laboratoire de Psychologie Environnementale, conducted a pilot study on water representations and perceptions in four french towns (Rennes, Limoges, Bordeaux et Paris) and six metropolis disseminated through the world. (Osaka, Brasilkia, Djakarta, Munich, Madrid and Ouagadougou). From the results of the french surveys, common elements of the representations were drawn up and used to build a general scheme of the representations ; then they permit to define some profiles of attitude towards water resources.Results of the other towns studies demonstrated the impact of cultural backgrounds upon representations, the major dimensions orientating the representations and the triggers usable in each culture to modify or reinforce public behaviours related to water. Results of both studies could be used to elaboration of information campaign directed to the public.